2016
DOI: 10.1097/phm.0000000000000441
|View full text |Cite
|
Sign up to set email alerts
|

Does 6-Month Home Caregiver-Supervised Physiotherapy Improve Post-Critical Care Outcomes?

Abstract: Carrying over regular bronchial hygiene techniques, physical activity, and exercise into the home after long critical care stays is safe and has a beneficial effect on respiratory muscles, decannulation, pulmonary function, and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…They demonstrated that an early neurorehabilitation protocol carried out during ICU period could increase chance of decannulation by more than 300% for tracheostomized patients affected by acquired brain injury. Vitacca et al ( 30 ) also confirmed the relationship between physiotherapy and probability of decannulation. They found that eighty-three% of critical care survivors underwent physical exercise were decannulated vs. 14% of controls.…”
Section: Discussionmentioning
confidence: 81%
“…They demonstrated that an early neurorehabilitation protocol carried out during ICU period could increase chance of decannulation by more than 300% for tracheostomized patients affected by acquired brain injury. Vitacca et al ( 30 ) also confirmed the relationship between physiotherapy and probability of decannulation. They found that eighty-three% of critical care survivors underwent physical exercise were decannulated vs. 14% of controls.…”
Section: Discussionmentioning
confidence: 81%
“…Duration of mechanical ventilation as an inclusion criterion varied from a minimum of 24 24,29,30 to 96 27 hours and an ICU length of stay ranging from 24 hours 31 to 20 consecutive days. 32 Two studies excluded patients who had a hospital admission or an ICU stay within a specified time period. 25,29,32 Exclusion criteria for these studies varied widely, but most excluded patients with pre-illness neurocognitive or psychiatric conditions such as dementia, substance abuse, suicidal ideation, or profound communication disorders.…”
Section: Samplementioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) and strain are seen in 21% of the caregivers [ 120 ]. A randomized trial, where caregivers provided respiratory physiotherapy at home, showed improvement of the cardiorespiratory status of the patients and their HRQoL (as measured with the EuroQoL 5D methodology) [ 121 , 122 ]. While the majority of the above-mentioned studies were not specifically designed for the very elderly patient group, it seems logical that the perceived strain, depressive symptoms and HRQoL will also translate to this group of caregivers.…”
Section: Long-term Outcomes Are the Best Criteria To Judge Appropriatmentioning
confidence: 99%